ANALYSIS OF CUSTOMER SERVICE QUALITY USING THE SERVICE QUALITY DATA METHOD AT BARAT LASE BARBERSHOP - David Krisman Hulu; Nita Marikena (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the quality of service to customers at Barbershop Barat Lase using the Service Quality (Servqual) method. This method assesses the gap between customer expectations and perceptions of the service provided based on five dimensions, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy. Data were obtained through distributing questionnaires to customers which were then processed using average calculations to determine the level of satisfaction. The number of consumers who were analyzed to fill out the questionnaire was 100 consumers. The results of the study showed that there was a difference between customer expectations and perceptions in several service dimensions, where most customers were satisfied with the service provided, although negative gaps were still found in several aspects. Thus, the results of this study can be an evaluation material for Barbershop Barat Laser in improving service quality to match customer expectations. From the application of the Service Quality method, it was found that 15 consumers were dissatisfied, 13 consumers were quite satisfied, 9 consumers were satisfied and 63 consumers were very satisfied.